Price Stickiness and Sectoral Inflation Persistence: Additional Evidence - Le Bihan, Herve; Matheron, J. (2012)
In this paper, using U.S. as well as French sectoral data and indicators of price rigidity, we reexamine the (lack of) relation between price stickiness and inflation persistence. This has recently been put forward by Bils and Klenow (2004) as evidence against time-dependent price setting models. We obtain that, when filtering out sector-specific shocks along the lines of Boivin, Giannoni, and Mihov (2009), and allowing for an alternative assumption on the marginal cost process, the case against the time-dependent Calvo model is substantially weakened. © 2012 The Ohio State University.